ANALISIS PERHITUNGAN PENERIMAAN DAN PENYETORAN PAJAK PENERANGAN JALAN DI KABUPATEN TANA TORAJA - Kaparang, Griya Clara; Pontoh, Winston; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Road Lighting Tax is one of the regional revenues whose revenues are very important for future improvement efforts. The purpose of this study is to find out whether the calculation of receipt and deposit of street lighting tax in Tana Toraja Regency is in accordance with the rules set or not, and the potential for acceptance and effectiveness. This research uses descriptive qualitative research. The results showed that the calculation of the receipt and deposit of street lighting tax in Tana Toraja Regency had proceeded with the rules set by the regional government, and the potential for its revenue and effectiveness in 2016-2017 had increased very well.